Effect of Papaver rhoeas hydroalcoholic extract on blood corticosterone and psychosocial behaviors in the mice model of predator exposure-induced post-traumatic stress disorder - Shima Shahyad; Hedayat Sahraei; Kamal Mousallo; Gila Pirzad Jahromi; Mohammad Taghi Mohammadi (Heliyon, 2023)
The function of hypothalamic-pituitary-adrenal (HPA) axis and psychosocial behaviors are affected in post-traumatic stress disorder (PTSD). Based on presence of several beneficial alkaloids in Papaver rhoeas (PR) plant, we assessed the effects of PR hydroalcoholic extract on blood corticosterone and psychosocial behaviors in the mice model of predator exposure-induced PTSD. Male NMARI mice were assigned into two main groups (control or PTSD) according to stress exposure (presence or absent of the predator). Each main group was divided into four subgroups according to treatment with the different doses of PR extract. Mice were treated intraperitoneally by PR extract at three different doses (1,5&10 mg/kg) 30 min before the beginning of test on days 1, 2&3. Corticosterone concentration determined in the blood samples on days 1, 3&21, and mice examined for the psychosocial behaviors on the third day. PTSD induction in mice by exposing to hungry predator increased blood corticosterone and changed the psychosocial and physiological behaviors. PR extract decreased blood corticosterone in PTSD mice on the third day as well as 21st day. Also, PR extract improved the psychosocial and physiological behaviors in PTSD mice. Moreover, PR extract increased blood corticosterone in control mice at a dose-response manner. PR extract is able to decrease blood corticosterone in PTSD condition and probably prevent the HPA hyperactivity in PTSD mice when exposed to the stress stimuli. Accordingly, decreased blood corticosterone by PR extract might be involved in improvement of the physiological and psychosocial behaviors in PTSD mice.